The multifunctionaly role of agriculture in Italy and its relation to gender - Navarra V. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
The female work in agriculture significantly contributes to promote the activities that are encountering important opportunities towards generating income and jobs. There are the following: agrotourism, organization of didactic activities within the farm, processing and sale of farm produce. The feminization process is affecting Italian agriculture. Women-run farms make up 30 percent of the total farms in the country. Their main objective is achieving a high standard of quality which consequently entails genuineness, hygiene and originality. The multifunctionality of the Italian agriculture can be categorized as productive, environmental, landscape and recreational. Within the rural policy framework, the recreational use of agricultural resources is one of the main objectives towards upgrading agricultural activities.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)